Weaning from mechanical ventilation - Alía, Inmaculada (BioMed Central, 2000)
Practice guidelines on weaning should be based on the results of several well-designed randomized studies performed over the last decade. One of those studies demonstrated that immediate extubation after successful trials of spontaneous breathing expedites weaning and reduces the duration of mechanical ventilation as compared with a more gradual discontinuation of ventilatory support. Two other studies showed that the ability to breathe spontaneously can be adequately tested by performing a trial with either T-tube or pressure support of 7 cmH(2)O lasting either 30 or 120 min. In patients with unsuccessful weaning trials, a gradual withdrawal for mechanical ventilation can be attempted while factors responsible for the ventilatory dependence are corrected. Two randomized studies found that, in difficult-to-wean patients, synchronized intermittent mandatory ventilation (SIMV) is the most effective method of weaning.